Development and Validation of a Robust and Straightforward LC-MS Method for Measuring Taurine in Whole Blood and Plasma of Dogs and Reference Intervals Calculation - Tommaso Furlanello; Riccardo Masti; Francesca Maria Bertolini; Valeria Ongaro; Andrea Zoia; Jose Sanchez del Pulgar (Animals)
Several studies have highlighted the essential role of taurine in maintaining the health of small animals, particularly dogs. Taurine deficiency has been linked to various health issues, especially in certain dog breeds. Therefore, accurately assessing taurine levels in canine blood is crucial for diagnosing and monitoring these conditions. In this study, we present the development of a novel liquid chromatography–tandem mass spectrometry (LC-MS/MS) method for rapidly quantifying taurine concentrations in dog whole blood and plasma. The method was validated according to current guidelines, showing excellent accuracy, precision, and sensitivity across a wide concentration range. Specifically, the limit of quantification was set at 80 nmol/mL for whole blood and 8 nmol/mL for plasma, ensuring the method’s reliability for both matrices. The application of this validated technique to blood samples of healthy dogs allowed for the establishment of reference intervals for taurine concentrations (148 to 495 nmol/mL for whole blood; 42 to 183 nmol/mL for plasma). Due to its robustness and simplicity, this method represents a valuable tool, supporting its routine use in health assessments and enabling more effective monitoring of taurine status in dogs.